Bifidobacterium animalis ssp. Lactis 420 Mitigates Autoimmune Hepatitis Through Regulating Intestinal Barrier and Liver Immune Cells - Zhang, Hongxia (Front Immunol, 2020)
Autoimmune hepatitis (AIH) is an immune-mediated inflammatory liver disease of uncertain cause. Accumulating evidence shows that gut microbiota and intestinal barrier play significant roles in AIH thus the gut–liver axis has important clinical significance as a potential therapeutic target. In the present study, we found that Bifidobacterium animalis ssp. lactis 420 (B420) significantly alleviated S100-induced experimental autoimmune hepatitis (EAH) and modulated the gut microbiota composition. While the analysis of clinical specimens revealed that the fecal SCFA quantities were decreased in AIH patients, and B420 increased the cecal SCFA quantities in EAH mice. Remarkably, B420 application improved intestinal barrier function through upregulation of tight junction proteins in both vitro and vivo experiments. Moreover, B420 decreased the serum endotoxin level and suppressed the RIP3 signaling pathway of liver macrophages in EAH mice thus regulated the proliferation of Th17 cells. Nevertheless, the inhibition effect of B420 on RIP3 signaling pathway was blunted in vitro studies. Together, our results showed that early intervention with B420 contributed to improve the liver immune homeostasis and liver injury in EAH mice, which might be partly due to the protection of intestinal barrier. Our study suggested the potential efficacy of probiotics application against AIH and the promising therapeutic strategies targeting gut–liver axis for AIH.